2021
DOI: 10.7554/elife.66968
|View full text |Cite|
|
Sign up to set email alerts
|

Mapping brain-behavior space relationships along the psychosis spectrum

Abstract: Difficulties in advancing effective patient-specific therapies for psychiatric disorders highlight a need to develop a stable neurobiologically grounded mapping between neural and symptom variation. This gap is particularly acute for psychosis-spectrum disorders (PSD). Here, in a sample of 436 PSD patients spanning several diagnoses, we derived and replicated a dimensionality-reduced symptom space across hallmark psychopathology symptoms and cognitive deficits. In turn, these symptom axes mapped onto distinct,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 132 publications
(222 reference statements)
0
29
0
Order By: Relevance
“…Notably, a recent whole-brain model using the dynamical mean-field quantitative description of excitatory and inhibitory neuronal populations as well as the associated synaptic gain function suggests that the effect of LSD on global brain connectivity can be best explained by the regional distribution and density of 5-HT2A receptors located on cortical pyramidal neurons [174]. A similar approach employing a transcriptomics-informed large-scale cortical model, including the expression level of various serotonergic and dopaminergic genes also found that modulation of pyramidal cell gain by 5-HT2A receptor activation accurately captures the LSDinduced GBC changes [119,144,145]. In addition, fitting to GBC in individual subjects revealed that the model also captures patterns of individual differences in LSD response that predict different aspects of the psychedelic experience [144].…”
Section: Effects Of Psychedelics On Brain Network Integrationmentioning
confidence: 94%
“…Notably, a recent whole-brain model using the dynamical mean-field quantitative description of excitatory and inhibitory neuronal populations as well as the associated synaptic gain function suggests that the effect of LSD on global brain connectivity can be best explained by the regional distribution and density of 5-HT2A receptors located on cortical pyramidal neurons [174]. A similar approach employing a transcriptomics-informed large-scale cortical model, including the expression level of various serotonergic and dopaminergic genes also found that modulation of pyramidal cell gain by 5-HT2A receptor activation accurately captures the LSDinduced GBC changes [119,144,145]. In addition, fitting to GBC in individual subjects revealed that the model also captures patterns of individual differences in LSD response that predict different aspects of the psychedelic experience [144].…”
Section: Effects Of Psychedelics On Brain Network Integrationmentioning
confidence: 94%
“…Our data-driven approaches suggest instead studying symptoms which are statistically rather than conceptually related. In fact, recent neuroimaging research has shown that PCA components of symptom scales were superior for identifying robust correlates of brain connectivity compared to traditional scale sub-scores 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Ji and colleagues took an alternative approach and examined a heterogeneous cohort of patients with psychosisspectrum disorders (PSD) with the aim of mapping cognition and psychopathology to imaging data trans-nosologically (Ji et al, 2021). In their initial analyses, they found that the clinical measures could be distilled down to five key components using principal components analysis and that these demonstrated substantially stronger relationships to global brain connectivity (GCB; a measure of FC) than the conventional psychometric measures.…”
Section: Molecular Information Links Pathophysiology Through To Netwo...mentioning
confidence: 99%